India and the world selected articles from IDSA journals - Sisodia, N. S.; Dutta, Sujit; Institute for Defence Studies and Analyses (New Delhi IDSA and Promilla & Co. in association with Bibliophile South Asia, 2005)
Contributed articles selected from IDSA journal and Strategic analysis, journals from India.
v. 1. Strategic thought : the formative years, 1965-1985.
Keywords: India -- Defenses; India -- Military policy; India -- Foreign relations